Insulin-like growth factor type 1 deficiency in a Moroccan patient with de novo inverted duplication 9p24p12 and developmental delay: a case report - Amasdl, Saadia (J Med Case Rep, 2016)
BACKGROUND: 9p duplication is a structural chromosome abnormality, described in more than 150 patients to date. In most cases the duplicated segment was derived from a parent being a reciprocal translocation carrier. However, about 15 cases with de novo 9p duplication have been reported previously. Clinically, this condition is characterized by mental retardation, short stature, developmental delay, facial dysmorphism, hand and toe anomalies, heart defects and/or ocular manifestations. CASE PRESENTATION: We report here the case of a 2-year-old Moroccan girl with a de novo duplication of 9p24 to p12. Clinical manifestations included failure to thrive, psychomotor delay, microcephaly, dysmorphic features, equinus feet, and umbilical hernia. Further clinical investigations showed an insulin-like growth factor type 1 deficiency. Banding cytogenetics identified a derivative chromosome 9, with an abnormally elongated short arm. Molecular cytogenetics based on multicolor banding probes characterized an inverted duplication 9p24 to p12 involving several genes especially an insulin-like growth factor binding protein named insulin-like growth factor binding protein-like 1, which seemed to be overexpressed, leading to the insulin-like growth factor deficiency in our patient. CONCLUSIONS: This study showed that insulin-like growth factor type 1 deficiency can be another feature of 9p duplication, suggesting a likely involvement of insulin-like growth factor binding protein-like 1 overexpression in growth delay. However, further studies of the gene expressions are needed to better understand the phenotype-karyotype correlations.